The most popular tourist destinations in Lombok Timur by univariate and bivariate analysis methods - Irwan Rahadi; Hasan Basri; Muhammad Adi Junaidi; Zaitun; Mugni; Dani Alfatwari (Institute of Computer Science (IOCS), 2022)
This study aimed to determine the popularity of tourist destinations in Lombok Timur with three investigated categories; the destination for islands, nature, and beaches. We use descriptive statistical approaches with univariate and bivariate methods. A random survey using google forms was distributed to 196 respondents within a particular time. Some questions developed in the questionnaire were prepared to screen respondents' perspectives on the popularity of tourist destinations visited with the python programming tool analysis. The data collected contains information about gender presented in the range and age. In addition, the level of education, address, and motive of the visit is compiled to collect data regarding the three categories of visits; mountains/villages/forests, beaches, and Islands. Furthermore, the length of stay, why people visit, how much money is spent during the visit, and whom they visit are essential parts of data collection. Data analysis concluded that Sembalun is the natural tourism category most in demand by people than other destinations such as Loyok, Tete Batu, and Kembang Kuning. From the beach category, pink beaches are the favorite destinations, and Gili Kondo is a popularly visited island.